Aqueous polyphenol semi-purified fractions from galls of Quercus infectoria increase ALP activity and mineralisation of hFOB 1.19 cells - Hermizi Hapidin,; Fairuza Munirah Mazlan,; Hasmah Abdullah,; Ima Nirwana Soelaiman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The galls of Quercus infectoria (QI) have been reported to possess numerous medicinal values and give a positive effect on bone metabolism. This study investigated the effects of semi-purified fractions of QI gall extract on the proliferation, alkaline phosphatase (ALP) activity, and mineralisation of human foetal osteoblast cell line (hFOB 1.19). The semi-purified fractions (fraction A and B) were prepared by column chromatography methods. MTT assay was used to measure cell proliferation activity to obtain half maximal concentration (EC50) of the cells treated with fraction A (phenolic components and contained amide), fraction B (phenolic components with the presence of alkene), and pamidronate (drug control). The most potent or lowest EC50 was further used to measure ALP activity in the treated and untreated cells at day 1, 3, 7, 10, and 14 by ELISA. Cell mineralisation was determined by von Kossa staining for phosphate depositions and Alizarin Red S staining for calcium depositions. The EC50 values for fraction A and B were 8.86 and 9.92 μg/mL, respectively, which showed a greater effect compared to the pamidronate (15.27 μg/mL). The ALP activity of both fractions in the treated cells were also greater compared to the two control groups (cells treated with pamidronate and untreated cells), starting from day 3 onwards. The calcium depositions appeared as red spots, while phosphate depositions appeared as black spots. Interestingly, the calcium depositions of cells treated with both fractions were higher than those of the two control groups. In conclusion, semi-purified fractions of QI gall extract enhanced proliferation, improved mineralisation, and increased ALP activity of hFOB 1.19 cells.